Determinants of financial institutions development under development of financial institutions act (DFIA)/ Salmah Hasan - Hasan, Salmah (Faculty of Business and Management, 2011)
An overwhelming amount of research has shown that financial development fosters economic growth and thus this paper aims to identify the determinants of financial institutions development under the Development of Financial Institutions Act (DFIA). This study investigates the determinants of financial institutions development using panel data analysis for the period 2001 to 2009 for financial institutions under DFIA which are Bank Pembangunan, SME Bank, AgroBank, Bank Simpanan Nasional (BSN), Import-Export Bank Malaysia Berhad and Bank Rakyat. The barriers for financial institutions include non performing loan that can be considered as banking crises. Other than that, ceilings on interest rates, because of high inflation rates, will lead discouraged saving and deposits. Besides, financial sectors are usually incomplete in as much as they lack a full range of markets and institutions that meet all the financing needs. The results show that loan disbursement and investment in securities are important determinants of financial development which lead to the positive relationship with the development while deposits and savings adversely influence financial development. The research findings were supplemented by journals and financial statements from secondary data. As a conclusion, in terms of financial development, considerable heterogeneity continues to exist around the world which creates competition among these financial institutions for economic development.